The Calculation of the Wedding Day (Babilangan) of the Banjar Community According to Islamic Law (Istihsan) - Akhmad Kamil Rizani; Muchimah Muchimah; Ahmad Irfan (Journal of Islamic Studies and Civilization, 2023)
Babilangan, a term widely known by the Banjar community as a practice of determining the day of marriage, is a tradition carried out for generations. The method used in calculating the day is by counting from the date of the first day of the beginning of the Hijriyah month, calculated from four angels: The first day was hit by the angel Gabriel. On the second day, the angel Mikail. The angel Israfil's third day and the angel Ijrail's fourth day. Thus, the first day of the Hijri month is related to the angel Gabriel, and the second is to the angel Mikail. On the first and second days, holding a wedding/marriage ceremony is very good.Meanwhile, the third and fourth days, related to the angels Israfil and Ijrail, are considered unlucky and could be better for carrying out a wedding/marriage event. The method used in this research is the normative juridical or library legal research method. The research approach is descriptive and analytical. The results of this study are the legal provisions of the babilangan tradition in determining the day of marriage, including the Shahih tradition, not violating the text, not eliminating maslahat, and not causing mafsadat, in the implementation of the tradition is a prayer described by action, namely seeking the pleasure of Allah.